ANALISIS PERSEPSI KARYAWAN TERHADAP BUDAYA ORGANISASI PADA PT AGRO JABAR PERSERODA - Dara Utami; Maya Setiawardani (Ebiz Prima Nusa, 2023)
Culture is a pattern of attitude of a group that becomes a habit and is passed down from generation to generation. This is also applied in the organization. Every organization has its own culture which differentiates one organization from another. Big companies like Google and Apple attribute their success to the organizational culture they have. Organizations are formed of three elements, namely people, goals, and structure. In addition to organizational culture which has a role in an organization, people in the organization also contribute to the activity of the organization. Perceptions of people or members of the organization can be used as a benchmark to continue to grow to be even better. The purpose of this study was to determine employee perceptions of organizational culture and the interrelationships of organizational culture dimensions at PT Agro Jabar by using quantitative research methods and data analysis. using descriptive statistical methods. The population is all employees of PT Agro Jabar with a census sampling technique sampling design. The results of the study show that of the six dimensions of organizational culture, three of them, namely outcome orientation, people orientation, and team orientation, fall into the 'very good' category, while the dimensions of adaptability, detail orientation, and integrity fall into the 'good' category.